(untitled) (Islamic Sciences Journal, 2024)
ABSTRACT Abdu al-Hamid Abu Suleiman is considered one of the intellectual personalities who have recently received attention from researchers working in the field of Islamic and human studies, due to the strength of his theses, which center on the renewal of the epistemological model and its connection to the issues and bets what the Islamic reality suffers from. An exploration of those turns and curves that formed along its historical path the theoretical, intellectual and methodological orientation of Abdul Hamid Abu Suleiman, may Allah the Almighty have mercy on him, has been investigated.